PENINGKATAN BUDAYA LITERASI PESERTA DIDIK MELALUI PROGRAM PENGUATAN LITERASI SEKOLAH DI SEKOLAH DASAR - Ariyani; Firsa Aprilia Anggraini (STKIP Subang, 2025)
ABSTRACT The school literacy strengthening program is a strategic effort to improve the literacy and numeracy culture of elementary school students. This activity aims to describe the implementation and impact of the School Literacy Strengthening Program on increasing students' reading interest, literacy skills, and numeracy. This research used a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The research subjects included teachers and students at SDN Bulu 02 and SDN Bulu 03, Pilangkenceng District, Madiun Regency. The literacy program was implemented through a 10–15-minute reading habit before class, mentoring in writing reading summaries, and numeracy reinforcement through educational games. The results showed an increase in reading interest, active student involvement in literacy activities, and the development of reading comprehension and basic numeracy skills. Furthermore, this program was able to foster reading habits and positive attitudes toward the learning process. Thus, the School Literacy Strengthening Program has proven effective in fostering a culture of literacy and numeracy in elementary schools and is recommended for continued implementation Keywords: school literacy 1, numeracy, literacy culture 2, elementary school 3. ABSTRAK Program penguatan literasi sekolah merupakan salah satu upaya strategis untuk meningkatkan budaya literasi dan numerasi peserta didik di sekolah dasar. Kegiatan ini bertujuan untuk mendeskripsikan pelaksanaan serta dampak Program Penguatan Literasi Sekolah terhadap peningkatan minat baca, kemampuan literasi baca-tulis, dan numerasi peserta didik. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Subjek penelitian meliputi guru dan peserta didik di SDN Bulu 02 dan SDN Bulu 03 Kecamatan Pilangkenceng, Kabupaten Madiun. Program literasi dilaksanakan melalui pembiasaan membaca selama 10–15 menit sebelum pembelajaran, pendampingan penulisan ringkasan bacaan, serta penguatan numerasi melalui media permainan edukatif. Hasil kegiatan menunjukkan adanya peningkatan minat baca, keterlibatan aktif peserta didik dalam kegiatan literasi, serta perkembangan kemampuan memahami bacaan dan numerasi dasar. Selain itu, program ini mampu membentuk kebiasaan membaca dan sikap positif terhadap proses pembelajaran. Dengan demikian, Program Penguatan Literasi Sekolah terbukti efektif dalam menumbuhkan budaya literasi dan numerasi di lingkungan sekolah dasar dan direkomendasikan untuk dilaksanakan secara berkelanjutan. Kata kunci: Literasi Sekolah 1, Numerasi, Budaya Literasi 2, Sekolah Dasar 3.